Manufaktur Handle Lifter Dengan Material SS400 - Abdul Rahman Agung Ramadhan; Abdul Muchlis; Patrik Agung Tri Fajar (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
A lifter is a device used to lift and move objects or materials from one place to another. Lifters are commonly used in the industrial world, examples of lifters are forklifts, cranes, stackers, drum lifters and hydraulic lifters. A lifter is a device used to lift and move heavy objects such as wooden pallets, boxes, or other industrial goods. One of the important components of a lifter is the handle which functions as a hand grip to move the lifter. A lifter handle is a handle or hand grip to push a lifter. The right material to use as a handle lifter is SS400. SS400 (Structural Steel) is a low carbon steel (mild steel) that complies with ASTM (American Society for Testing Materials) A36 or JIS (Japanese Industrial Standards) G3101 standards. The Handle Lifter manufacturing process includes the cutting process, namely cutting from an initial length of 6 meters to 150mm. The milling process is cutting lengths and thicknesses with a length of 135mm with a first thickness of 13mm, a second thickness of 15mm and a third thickness of 13mm. Drilling process, where this process involves making a hole with a diameter of 10mm. The grinding process is a finishing process that aims to smooth uneven surfaces. And finally, Quality Control is carried out to check whether or not the goods being produced are suitable. Based on the calculation results, the productivity value for making Handle Lifters in 1 day was obtained, where the working hours used were 8 hours, resulting in 17 Handle Lifters.